Endothelial cell autophagy in homeostasis and cancer. Issue 11 (24th April 2021) - Verhoeven, Jelle; Baelen, Jef; Agrawal, Madhur; Agostinis, Patrizia
Abstract : Autophagy, the major lysosomal pathway for the degradation and recycling of cytoplasmic materials, is increasingly recognized as a major player in endothelial cell (EC) biology and vascular pathology. Particularly in solid tumors, tumor microenvironmental stress such as hypoxia, nutrient deprivation, inflammatory mediators, and metabolic aberrations stimulates autophagy in tumor‐associated blood vessels. Increased autophagy in ECs may serve as a mechanism to alleviate stress and restrict exacerbated inflammatory responses. However, increased autophagy in tumor‐associated ECs can re‐model metabolic pathways and affect the trafficking and surface availability of key mediators and regulators of the interplay between EC and immune cells. In line with this, heightened EC autophagy is involved in pathological angiogenesis, inflammatory, and immune responses. Here, we review major cellular and molecular mechanisms regulated by autophagy in ECs under physiological conditions and discuss recent evidence implicating EC autophagy in tumor angiogenesis and immunosurveillance. Abstract :